Terrestrial impact sites as field analogs for planetary exploration - Lambert, Philippe; Reimold, Wolf Uwe (Frontiers in Astronomy and Space Sciences, 2023)
Terrestrial impact structures provide the only analogues for hands-on astronaut training or robotic exercises in preparation for field work on other planetary surfaces. Impact structures do not only represent the dominant surface features on, inter alia, the Moon, Mars, or asteroids, but they are also crucial for basic geoscientific surface analysis, subsurface geological studies, and analysis of sites of possible exobiological evidence or economic resources for future colonization of other planetary bodies. We assess 11 terrestrial impact structures of varied age, type, size, and erosion level, the majority of which have already served for astronaut or geoscientist/student training purposes, for their suitability as possible impact geological training sites. This evaluation is achieved through: 1- Practical Criteria: Ries, Rochechouart, and Steinheim score highest, with a small advantage for Ries. Sudbury and Meteor Crater score similarly, yet much lower than the leaders, with Vredefort in between. Talemzane and Araguainha are just below Meteor Crater. Clearwater West, Haughton and Mistastin are by far the least suitable ones. 2- Geological Criteria: The 3 Northern Canada structures and Steinheim are at the end of the record, yet only 23-39 % below Ries, the leader, which is closely followed by Araguainha (only 2% below Ries). Although the Northern Canada sites compare in size and type to the younger and less eroded Ries and Araguainha (older and more eroded) structures, the diversity of Impact Features and Lithologies and the outcrop situation are less favorable. Considering only the Geological Features and Lithologies factors, Rochechouart gets the highest mark, followed by Araguainha, Sudbury, Vredefort, and Ries. In view of the targeted objective, the analogue testing experiment places Ries and Rochechouart in 1st and 2nd position. Steinheim and Vredefort score almost the same in 3rd to 4th position. The 3 Northern Canada sites score the lowest. Based on their accessibility, relative proximity to each other, and remarkable complementarity in terms of crater type and size, and in terms of Impact and Target Features and Lithologies, the combination of the 3 leading structures (Ries-Rochechouart-Steinheim) may represent the most appropriate target for analogue training purpose, from anywhere in the world.